Prevalence of Type 2 Diabetes Mellitus and Adherence to Anti Diabetic Treatment in an Urban Population - Lyngdoh, Markordor; Romola, Pukhrambam (National Journal of Community Medicine, 2021)
Context: Diabetes is the largest health emergency of the 21st century. Among the diagnosed patients, a large number do not adhere to treatment. Non-adherence leads to increase of morbidity and mortality due to a compromise in the safety and effectiveness of the treatment. This study aimed to determine the prevalence of Type 2 Diabetes Mellitus (t2DM) among adults ≥ 30 years old in an urban community in Imphal West and to assess the adherence to anti diabetic treatment. Methodology: This study was conducted in an urban area in Imphal between 2016 –2018 among adults ≥ 30 years. Data was collected using an interview schedule and analysed using IBM SPSS for Windows, Version 21.0. Results: The prevalence of t2DM among the participants was 14.4% while pre-diabetes was 30.8%. Diabetes was associated with males, increase in age, smoking, tobacco use, alcohol use and family history of diabetes. Adherence to exercise (0%), diet (11.1%), foot-care (0%), RBS monitoring (3.7%), medication (85.2%), no smoking (100%). Conclusions: The prevalence of t2DM in Imphal is 1.6 times more than the national average while the prevalence of pre-diabetes was even higher. All of the previously diagnosed diabetic patients had little or no adherence to lifestyle modifications.